The Role of Positive 3-H Words in Peacebuilding and Engagement in EFL/ESL Classes - Shi, Xiaojing (Frontiers in Psychology, 2021)
This review aimed at investigating the role of help, hope, and harmony formally known as positive 3H on students’ engagement and peacebuilding. To start with, a definition for positive 3-H was presented coupled with the role it plays in language learning contexts. Then the way both inner peace and interpersonal peace have been applied in the learning process to build peace is discussed. Following that, the effects of positive 3-H on students’ engagement and peacebuilding through raising some relevant activities are dealt with. Finally, implications and further directions are put forward.